PRELIMINARY INTERPRETATION FOR GEOTHERMAL POTENTIAL AREA USING DEM AND LANDSAT OLI 8 IN MOUNT ENDUT - MAHARANI, ALYA; SALSANUR, VISKA; HILAL, ALBI; APRILIAN, YOGA (Fakultas Teknik Geologi Universitas Padjadjaran, 2021)
Regard to the increasing need for fossil energy in Indonesia, it is necessary to explore alternative energy. For example is geothermal energy, which is known as a sustainable and eco-friendly energy source. Indonesia is one of the countries with the most substantial geothermal potential reaching 23.9 GW. Therefore, this study using the remote sensing method to predict potential areas for geothermal systems in the Mount Endut, Lebak, Banten. The research using Landsat 8 OLI for analysis Normalized Difference Vegetation Index (NDVI) and Land Surface Temperature (LST), along with DEM imagery is used for Fault Fracture Density (FFD) analysis. The results of Land Surface Temperature (LST) analysis showed the highest value in the northern and middle part of the research area with a value of 33.7°C. This is related to the results of the NDVI analysis, which areas has lower values in the northern and middle areas with values about 0.36 - 0.06. The lineament mostly has a northwest-southeast direction, with the highest value of the lineament density is 2.69 km / km2, mostly located in the middle part of the research area that can be related to the weakest zone as a geothermal path to the surface. Based on the results, it shows the relationship between the LST is the opposite of the NDVI value. Thus, it can be concluded that the area which has geothermal potential is located from western to the middle of the research area, which is correlated with the presence of manifestation regarding to hot springs.